The Luminaries - Dennard, Susan (Tor Teen, 2022)
"Winnie Wednesday, an outcast from the Luminaries, is determined to restore her family's good name by taking the deadly hunter trials on her sixteenth birthday, but when she turns to her former best friend Jay Friday for help, they discover a danger lurking in the forest no one in Hemlock Falls is prepared for"--